Peranan Guru dalam Pendidikan Islam - Qolbi Khoiri; Ardianti Yunita Putri (GHAITSA : Islamic Education Journal, 2024)
The teacher is the most important role in the ongoing learning process because a teacher will change behavior and improve the quality of students to become better individuals. The task of a teacher is to guide, educate and direct students to always be devoted to Allah SWT. This article aims to find out that teachers have a higher and special role in Islamic education. This research uses library data sources in the form of books, journals and other sources collected from several references related to the title of this article. The technique used in collecting data is by looking for reference sources related to the discussion of this article. The results of this research show that teachers have a higher role in Islamic education. Allah will also give higher positions and degrees to people with knowledge. A teacher has an obligation to create the nation's children into intelligent human beings who have good morals.